(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
Students’ poor ability in completing geometry questions is one of the crucial problems in mathematics education. In this mixed method research, Think-Talk-Write cooperative learning was used to enhance seventhgrade students’ ability in completing geometry questions. Samples were 35 seventh grade students in one of junior high school in East Java. Instruments were students’ worksheets (LKS), written test, as well as observation sheets. Think-Talk-Write learning was conducted in two learning sessions. Results showed that Think-Talk-Write learning increased students’ ability in completing geometry questions, both in completing questions in the LKS and in the written test. Steps in Think-Talk-Write learning help the students to reflect, organize, and improve their understanding so that they are able to answer the given geometry questions better. In addition to the contribution of each step in Think-Talk-Write learning itself, teacher also contributed to students’ improved ability in completing geometry questions, especially in terms of detecting and guiding the students’ to overcome difficulties in completing geometry questions. Buruknya kemampuan siswa dalam menyelesaikan soal-soal geometri merupakan salah satu permasalahan krusial di bidang pendidikan matematika. Pada penelitian metode campuran ini, strategi pembelajaran kooperatif Think-Talk-Write digunakan untuk meningkatkan kemampuan siswa kelas VII dalam menyelesaikan soal-soal geometri. Sampel adalah 35 siswa kelas tujuh di salah satu sekolah menengah pertama di Jawa Timur. Instrumen penelitian adalah lembar kerja siswa (LKS), tes tertulis, maupun lembar observasi. Pembelajaran Think-Talk-Write dilaksanakan dalam dua sesi pembelajaran. Hasil menunjukkan bahwa pembelajaran Think-Talk-Write mampu meningkatkan kemampuan siswa dalam menyelesaikan soal-soal geometri, baik soal-soal yang diberikan pada LKS maupun saat tes tertulis. Tahapan-tahapan pada strategi pembelajaran Think-Talk-Write membantu siswa untuk merefleksikan, mengorganisasikan, dan memperbaiki pemahamannya sehingga mampu menjawab soal-soal geometri yang diberikan dengan lebih baik. Selain kontribusi dari tahapan-tahapan pembelajaran Think-Talk-Write itu sendiri, guru juga berkontribusi terhadap peningkatan kemampuan menyelesaikan soal-soal geometri khususnya dalam hal mendeteksi dan membimbing siswa untuk mengatasi kesulitan-kesulitan yang mereka alami dalam menyelesaikan soal-soal geometri.